Pluralism in Tuning the Contemporary Arab Oud Strings - Egyptian and Iraqi Schools Model: فراس ياسين جاسم (Al-Academy, 2019)
The Egyptian and Iraqi schools are one of the most important musical schools in the style of playing the oud. The influence of the style of these schools extended in the contemporary Arab world, and there were important names that emerged characterized with their style of playing. Thus, the ways of tuning the strings of oud varied between the two schools because of the difference in the ways of playing and the difference in the style of expression. The aim of the research was to identify the pluralism of the variable tunings of the strings of the contemporary Arab oud of the Egyptian and Iraqi schools, along the historical period extending from the late nineteenth and twentieth centuries to the present time. The oud has been classified into (five, six and seven strings). The samples representing the two schools were chosen intentionally, according to the variable in the tuning, and according to the classifications of the type of oud. The traditional five-string tuning of the oud has been relied on, derived from the quartet equation of Al-Kindi, as a principle to know the variable in the tuning of the contemporary Arab Oud. Types of tuning in both schools and the extent of similarity and difference between them linked to the method of performance and expression of the two schools have been identified.